Unsteady Magnetohyrodynamics Natural Convection Dissipative Flow Through an Inclined Plate - Dada, M. S.; Aladesusi, O.S. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2015)
This study investigates the effects of viscous dissipation on an unsteady two-dimensional magnetohyrodynamic (MHD) natural convection through an inclined plate. The governing partial differential equations together with the boundary conditions are transformed into a system of dimensionless coupled partial differential equations. An implicit finite difference method is used to solve the dimensionless equations. The effects of various fluid parameters on velocity, temperature, concentration distribution are separately presented in graphical forms and discussed.